New chromosome rearrangements from conidia of Neurospora wild type OR23-1VA - David D. Perkins; J. A. Kinsey (Fungal Genetics Reports, 1993)
In experiments of Perkins, Kinsey, Asch and Frederick (1993 Genetics 134:729-736), new chromosome rearrangements were recovered with a frequency of 10% or more among mitotically stable transformants of am strains, whereas rearrangements were rare (< 1%) in cultures from untransformed regenerated protoplasts of the same strains.